Spending habits among Diploma Muamalat students in Academy of Contemporary Islamic Studies (ACIS) UiTM Puncak Alam / Firdaus Harman. - Harman, Firdaus (2019)
Students' spending habits today have become a major concern in our society in the face of rising bankruptcy cases and social issues among younger generations in Malaysia, frequently associated with their financial instability due to poor individual financial management. Nowadays students' spending habits is quite different from before, raising a doubt as to what could be the students' spending factors today. The purpose of this study is to identify factors affecting students' spending habits alongside to investigate their awareness on financial literacy and propose a set of guidelines in proper financial practices for them. The respondents of this research are students from Diploma Muamalat of Academy of Contemporary Islamic Studies (ACIS) in UiTM Puncak Alam, Selangor, the method used is a Quantitative Approach by survey through questionnaires which are adapted for this study. Ironically, being knowledgeable and having skill in financial field, especially with respect to Islamic financial product, would be a great asset to them. The findings from this research were able to determine the factors affecting spending habits among the students and their awareness on financial literacy. Based on the result of the study, the researcher made up several recommendations in encouraging proper financial practices for the students. The results of this study are important to assist higher education institutions in creating and planning financial education framework that can be offered to students at the university and college. The results of this study are important to assist higher education institutions in creating and planning financial education framework that can be offered to students at the university. The implications and recommendations are provided.